Contributions in mathematical physics:a tribute to Gerard G Emch - Ali, S Twareque; Sinha, Kalyan B. (New Delhi: Hindustan Book Agency, 2007)
The articles featured here are a small yet representative sample of the breadth and reach of some of the ideas from mathematical physics.It is also a testimony to the impact that Professor Emch's work has had on several generations of mathematical physicists as well as to the diversity of mathematical methods used to understand them.
Includes bibliographical references.
Keywords: Mathematical physics; Mathematics